2017
DOI: 10.1016/j.orcp.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Depression and body mass index, differences by education: Evidence from a population-based study of adult women in the U.S. Buffalo-Niagara region

Abstract: The relationship between obesity and depression is well described. However, the evidence linking depression and body mass index (BMI) across the broad range of body size is less consistent. We examined the association between depressive symptoms and BMI in a sample of adult women in the Buffalo-Niagara region between 1997 and 2001. Using logistic regression, we investigated whether increased weight status beyond normal-weight was associated with a higher prevalence of depressive symptoms, and if educational at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…And regarding the significant morbidity of depression with obesity, various studies found a close association between obesity and depression [32][33][34][35][36][37] due to the positive relation between depression and emotional eating [38] as well as the associated poor body image, lack of competence, interpersonal problems, and internalization of weight bias with obesity [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And regarding the significant morbidity of depression with obesity, various studies found a close association between obesity and depression [32][33][34][35][36][37] due to the positive relation between depression and emotional eating [38] as well as the associated poor body image, lack of competence, interpersonal problems, and internalization of weight bias with obesity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study reflected that women with university degrees had a 2.1 kg/m 2 lower BMI compared to that of women with lower education levels because of being more preoccupied by body image issues and leading a higher energy expenditure lifestyle [61]. Also, the prevalence of depression was found to be associated with lower educational level [33,62], lower economic status, and metabolic syndrome than the control group [62].…”
Section: Educational Level In Relation To Obesity and Its Psychiatricmentioning
confidence: 98%
“…SES of patients with CMDs was inversely related to the prevalence of depression in both males and females, although the association was stronger in females [41]. In the other study, which was a population-based study of adult females in the United States Buffalo-Niagara region, the prevalence of depression plus obesity was higher in more educated women than in less educated women (OR=2.15, 95% CI 1.27-3.62) [42]. By contrast, the combination of education level and MS was more strongly associated with depression in males than in females in our study.…”
Section: Discussionmentioning
confidence: 86%
“…We observed similar trends in all three models. Two previous studies reported the prevalence of depression and its comorbidities according to SES [41,42]. In the MultiCare Cohort Study, lower SES was associated with a higher prevalence of chronic conditions, such as cardiovascular and metabolic disorders (CMDs), as well as the composite outcome of depression, anxiety, somatoform disorders, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…SES was inversely related to the composite outcome including depression in both males and females, although the association was stronger in females [41]. In the other study, which was a population-based study of adult females in the United States Buffalo-Niagara region, the likelihood of depression plus obesity was higher in more educated women than in less educated women (OR = 2.15, 95% CI 1.27-3.62) [42]. By contrast, the combination of education level and MS was more strongly associated with depression in males than in females in our study.…”
Section: Discussionmentioning
confidence: 90%